PROPOSAL OF AN INNOVATION POLICY FOR THE FEDERAL UNIVERSITY OF GRANDE DOURADOS (Comunicação & Inovação, 2023)
This research aimed to propose an Innovation Policy for the Federal University of Grande Dourados. UFGD is a public ICT and by law must have an innovation policy in place. To reach the proposed objective the following data collection techniques were used: bibliographic and documental research, benchmarking and interviews. Based on the results obtained it was possible to prepare a draft proposal for the implementation of an innovation policy at UFGD, as well as a process model to assist managers in implementing this policy.
Keywords: Innovation Policy; Public University; Cooperation